Pelatihan Penyusunan Laporan Keuangan Berbasis Microsoft Excel Menuju UMKM Naik Kelas - Dian Sulistyorini Wulandari; Nining Yuningsih; Erlina Widayanti; Salmiya Kartika (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Micro, small and medium enterprises (MSMEs) have a crucial role in the Indonesian economy. However, MSMEs often face a number of obstacles caused by certain factors, such as low levels of education, lack of understanding of information technology, and unreliability in presenting financial reports. The aim of this service activity is to provide training to MSMEs who are members of the OKE OCE Melawai program regarding simple bookkeeping using the Excel application, in accordance with SAK UMKM standards. This activity involves several stages, including a pre-assessment questionnaire, tutorial, practical training, and a simple accounting assessment. In the initial investigation stage before implementing community service activities, it was discovered that the majority of OKE OCE Melawai MSMEs still used manual ledgers to manage their accounts, which ultimately affected the quality of financial reporting. A total of 46 MSMEs assisted by OKE OCE Melawai participated in this activity enthusiastically. The activity went well, and it is hoped that it will produce Microsoft Excel-based financial reports as the output of this community service. Thus, it is hoped that OKE OCE Melawai's MSMEs can improve their basic skills and understanding in the field of accounting, and be able to present quality financial reporting data using Microsoft Excel according to accounting standards.